2014
DOI: 10.11648/j.aff.20140302.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alternate Wetting and Drying (AWD) Irrigation for Boro Rice Cultivation in Bangladesh

Abstract: Abstract:A field experiment was conducted at the Bangladesh Rice Research Institute to find out possible effects of alternate wetting and drying irrigation (AWDI) on the yield, water use and water use efficiency (WUE) of Boro rice. The experimental plots were laid out with 2 factors RCBD combining two modern varieties of rice viz., BRRI dhan29 and BRRI hybrid2, which received four irrigation treatments randomly and was replicated thrice. The treatments ranged from continuous submergence (T 1 ) of the field to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
2
15
0
1
Order By: Relevance
“…The significantly lowest panicle weight was registered by the crop in I 8 (AWD irrigation regime of 3 cm from transplanting to PI stage and thereafter 5 cm up to physiological maturity when the water level drops to 15 cm below ground level in field water tubes) on a pooled basis. These results were similar to previous findings for rice subjected to water stress conditions (Boonjung and Fukai, ; Bakul et al, ; Azarpour et al ., ; Rahman and Sheikh, ; Kumar et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The significantly lowest panicle weight was registered by the crop in I 8 (AWD irrigation regime of 3 cm from transplanting to PI stage and thereafter 5 cm up to physiological maturity when the water level drops to 15 cm below ground level in field water tubes) on a pooled basis. These results were similar to previous findings for rice subjected to water stress conditions (Boonjung and Fukai, ; Bakul et al, ; Azarpour et al ., ; Rahman and Sheikh, ; Kumar et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Various experiments have reported water saving in AWD plots of 20% (Oliver et al., ; Paul et al. , ), while Rahman and Bulbul () found that all of the AWD treatments significantly increased yield when compared to the standing water control plots. This contrasts, however, with Oliver et al.…”
Section: Alternate Wetting and Dryingmentioning
confidence: 99%
“…The decision over when to start AWD will significantly impact the water saving achieved by the practice, but the literature is not yet decided on a definite answer. It is also unclear as yet what this standing water is for, whether it is to reduce weeds (Rahman & Bulbul, ), to aid crop establishment (Lampayan, Samoy‐Pascual, et al., ), to ensure maximum nitrogen uptake before water is allowed to drain (Linquist et al., ), or perhaps a combination of these factors.…”
Section: Alternate Wetting and Dryingmentioning
confidence: 99%
See 1 more Smart Citation
“…Di sebagian besar daerah Asia, tanaman padi tumbuh kurang optimum akibat kelebihan air atau kekurangan air karena curah hujan yang tidak menentu dan pola lanskap yang tidak teratur (Rahman and Bulbul, 2014).…”
unclassified